Stability Of Islamic Commercial Banks In Indonesia: Company Size, Profitability, And Efficiency - Hasanah, Annisa Nur; Umiyati, Umiyati (LPPM ISNJ Bengkalis, 2024)
This study aims to analyze the effect of company size, profitability, and efficiency on the stability of Islamic commercial banks (ICB). This study uses a quantitative approach. The population of this study is Islamic commercial banks, and the sampling technique used is purposive sampling, obtained from four ICBs. The data source used is secondary data from each ICB's financial statements. The data analysis technique used is panel data regression analysis using e-views software version 13. The results of this study indicate that company size positively affects ICB's stability. However, profitability negatively affects ICB's stability. In contrast, efficiency does not affect ICB's stability. This study can complement existing theories, especially regarding the effect of size on company stability, and can be a reference for further research. Practically, this study can be a reference for banks in maintaining the stability of company operations in terms of company size and profitability.